Anticancer Activity of Some Medicinal Plants: Minireview - Al-Dahmoshi, Hussein O.M.; Sultana, Sabira; Mahdi, Zena Abdul-Ameer (Jour Med Resh and Health Sci, 2023)
Cancer is a life-threatening illness that causes irreversible cell growth and is a serious public health issue worldwide. After heart disease, it is the second biggest cause of death. People choose to use natural herbs to cure cancer due to the high mortality rate caused by the disease. Since the dawn of civilization, plants have not been used to cure illnesses. Cancer prevention and treatment have greatly benefited from medicinal plants. For a long time, phytochemical research on medicinal plants has contributed to the development of novel vaccines. This article will look at some of the medicinal plants used to cure cancer, as well as vaccines used by people around the world. This study can help researchers determine the extent to which their cultures are used in clinical trials for various diseases and other toxicological investigations.